Studying independent Kcna6 knock-out mice reveals toxicity of exogenous LacZ to central nociceptor terminals and differential effects of Kv1.6 on acute and neuropathic pain sensation - Peck, LJ; Patel, R; Diaz, P; Wintle, YM; Dickenson, AH; Todd, AJ; Calvo, M; Bennett, DLH (Society for Neuroscience, 2021)
The potassium channel Kv1.6 has recently been implicated as a major modulatory channel subunit expressed in primary nociceptors. Furthermore, its expression at juxtaparanodes (JXP) of myelinated primary afferents is induced following traumatic nerve injury as part of an endogenous mechanism to reduce hyperexcitability and pain-related hypersensitivity. In this study we compared two mouse models of constitutive Kv1.6 knock-out achieved by different methods: traditional gene trap via homologous recombination, and CRISPR-mediated excision. Both Kv1.6 knock-out mouse lines exhibited an unexpected reduction in sensitivity to noxious heat stimuli, to differing extents: the Kv1.6 mice produced via gene trap had a far more significant hyposensitivity. These mice (Kcna6lacZ) expressed the bacterial reporter enzyme LacZ in place of Kv1.6 as a result of the gene trap mechanism and we found that their central primary afferent presynaptic terminals developed a striking neurodegenerative phenotype involving accumulation of lipid species, development of ‘meganeurites’ and impaired transmission to dorsal horn wide dynamic range (WDR) neurons. The anatomical defects were absent in CRISPR-mediated Kv1.6 knock-out mice (Kcna6 -/-) but were present in a third mouse model expressing exogenous LacZ in nociceptors under the control of a Nav1.8-promoted Cre recombinase. LacZ reporter enzymes are thus intrinsically neurotoxic to sensory neurons and may induce pathological defects in transgenic mice, which has confounding implications for the interpretation of gene knock-outs using lacZ. Nonetheless, in Kcna6 -/- mice not affected by LacZ, we demonstrated a significant role for Kv1.6 regulating acute noxious thermal sensitivity, and both mechanical and thermal pain-related hypersensitivity after nerve injury.